2021
DOI: 10.17219/acem/140842
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of methotrexate and low-dose steroid therapy in the treatment of idiopathic granulomatous mastitis

Abstract: Dalbaşı E, Akgül Ö. The effectiveness of methotrexate and low-dose steroid therapy in the treatment of idiopathic granulomatous mastitis [published online as ahead of print on September 9, 2021].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…GLM may involve a single breast or both breasts synchronously, although bilateral involvement is rarer, occurring in only 1% of cases ( 9) in one study. In another case series of 62 patients, Dalbaşı et al (41) reported that 30 (48.38%) patients had lesions only in the right breast, 26 (41.94%) patients had lesions only in the left breast, and 6 (9.68%) patients had lesions in both breasts.…”
Section: Localizationmentioning
confidence: 95%
“…GLM may involve a single breast or both breasts synchronously, although bilateral involvement is rarer, occurring in only 1% of cases ( 9) in one study. In another case series of 62 patients, Dalbaşı et al (41) reported that 30 (48.38%) patients had lesions only in the right breast, 26 (41.94%) patients had lesions only in the left breast, and 6 (9.68%) patients had lesions in both breasts.…”
Section: Localizationmentioning
confidence: 95%
“…The recommended dose can be from 7.5 to 25 mg/week, but several studies have suggested that the initial dose is 15 mg/week. The remission rate can be as high as 81-93%, and the average course of treatment is 8-10 months (132,133).…”
Section: Othersmentioning
confidence: 99%
“…There are multiple management modalities of IGM with various advantages and drawbacks, so the treatment of choice is still under debate [6]. The current treatment options are used alone or in combination, including surgical intervention, immunosuppressive agents, steroids, antibiotics, close observation, and herbal treatment like Saussurea Costus (S. costus) which has broad bioactivity against bacterial and mycological infections [7][8][9]. In addition, IGM is associated with a high rate of relapse following treatment, and it requires intensive care and follow-up [10].…”
Section: Introductionmentioning
confidence: 99%